Hamas Rule in Gaza: Human Rights under Constraint - Mukhimer, T. author. aut Link
VIII, 158 p.
Keywords: Developing a normative framework for evaluating non-state actors in the absence of formally binding obligations, this study is the first detailed human rights analysis of Hamas conduct and governance in the Gaza Strip.